PERSONALITY DEVELOPMENT AMONG STUDENTS IN EDUCATIONAL INSTITUTIONS THROUGH NATIONAL CADET CORPS ACTIVITIES - Garg, Commodore Vijesh; Sam, Annie (International Journal of Psychosocial Rehabilitation, 2020)
The twenty first century has witnessed a drastic change due to globalization and competitiveness in all spheres. Due to fierce competition at all levels, besides professional field, personality traits and skills are often put to test for comparison of merit. Our university education curriculum does not cater for the development of student’s overall personality with basic skills by remaining focused on exam centered stream- related areas. Despite qualifying for a degree, most students lack in self -confidence, basic leadership, sense of discipline, creativity, critical thinking, communication skills, team spirit, sense of little adventure, time management & adaptations. These are the essential traits and skills expected in a proactive, responsible educated youth today in society, to bring attitudinal change .The National Cadet Corps (NCC) was established in India in 1948 with a vision to develop the overall personality of youth. The NCC training activities provide opportunities and motivate young students to improve their general knowledge, communication skills, soft skills, life skills, character building & traits of good personality. These basic leadership qualities and managerial skills will also prepare the young graduates in taking up as confident leaders and entrepreneurs. This research paper has attempted to establish the relationship and importance of National Cadet Corps activities in developing good personality traits and skills among students using hypothesis testing and recommends activities of National Cadet Corps to be made as mandatory for all as part of education curriculum till graduation in India.